The Impact of Financial Decisions on the Profit Margin of Selected Commercial Bankas in Lagos, Nigeria (Global Journal of Management and Business Research, 2018)
decisions have on the profit margin of commercial banks in Lagos, Nigeria. Seven commercial bank were selected spanning the first, second and third generation banks from 1995-2004. 375 questionnaires were administered on the management cadre of the selected banks of which 350(93%) were fully completed and returned. Secondary data was extracted from the annual reports of the selected banks. The objectives were addressed using(i) descriptive statistics, (ii) multiple linear regression analysis (iii) logit regression and tobit models. The results of the regression analysis showed that only three banks recorded a significant relationship between the profit margin and financial decisions. They are Union bank, Chartered bank and Intercontinental bank representing the first, second and new generation banks Their F-values stood at 6.797, 45.043 and 8.412 respectively. In Chartered bank there was significant relationship between the profit margin and financial decisions at both .01% and .05% levels respectively. While in the other banks the results showed otherwise. The logit regression results also showed that profit margin was greatly influenced by capital (11.88), dividend yield (-3.70), profit margin indicator (17.53) and performance (-2.88) at 1% level of significance. The study shows that the relationship between financial decisions and the profit margin was very strong, thus, sound financial decisions are very crucial for better profit margins. It is thus recommended that banks should build and implement better strategies to help meet with the global challenges facing them to get the desired results of adequate profits.
Keywords: commercial banks; financial decisions; financial management; profits; profit margins; regression analysis